CAMINHOS DA DESPOLUIÇÃO: AVALIAÇÃO DO RIO SÃO DOMINGOS NO PERÍODO DE 2000 A 2010 - Tambellini, Cássia Aparecida; Silva Sé, João Alberto da; Abdo, Maria Teresa Vilela Nogueira (Electronic Journal "Fórum Ambiental da Alta Paulista", 2011)
.